Integrating Technology in Teaching Methods: Academic Perspective (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper aims to share findings on the importance of using ICT (Information and Communication Technology) tools in their classrooms. The objective is to gain a clearer understanding of the resources available, the training and support teachers receive, and how effectively they integrate technology into their teaching and professional development. It is an insightful trip to discover how these factors shape the teaching experience!